2014
DOI: 10.1038/mt.2013.245
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Gene Silencing Using Polymerized siRNA/Thiolated Glycol Chitosan Nanoparticles for Rheumatoid Arthritis

Abstract: Among various proinflammatory cytokines involved in the pathogenesis of rheumatoid arthritis (RA), tumor necrosis factor (TNF)-α plays a pivotal role in the release of other cytokines and induction of chronic inflammation. Even though siRNA has the therapeutic potential, they have a challenge to be delivered into the target cells because of their poor stability in physiological fluids. Herein, we design a nanocomplex of polymerized siRNA (poly-siRNA) targeting TNF-α with thiolated glycol chitosan (tGC) polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 39 publications
2
64
0
Order By: Relevance
“…However, the potential use of siRNA therapy in RA has not progressed beyond the preclinical models. These studies range from local electroporation to deliver siRNA directly into joint tissue of arthritic mice to several studies of systemic delivery of liposome-or polymer-based nanoparticles delivering anti-cytokine or anti-cytokine receptor siRNA (25)(26)(27)(28)(29)(30). Although these preclinical studies all showed efficacy, potential off-target effects and immune responses were rarely fully addressed.…”
Section: Resultsmentioning
confidence: 99%
“…However, the potential use of siRNA therapy in RA has not progressed beyond the preclinical models. These studies range from local electroporation to deliver siRNA directly into joint tissue of arthritic mice to several studies of systemic delivery of liposome-or polymer-based nanoparticles delivering anti-cytokine or anti-cytokine receptor siRNA (25)(26)(27)(28)(29)(30). Although these preclinical studies all showed efficacy, potential off-target effects and immune responses were rarely fully addressed.…”
Section: Resultsmentioning
confidence: 99%
“…[8,10,13,[21][22][23]25,38,39]. MTC conjugates were rationally designed in our previous investigation and were demonstrated to overcome the intestinal absorption barrier as well as the transfection barrier in macrophages [13].…”
Section: Discussionmentioning
confidence: 99%
“…83 Downregulation of TNF-α-induced inflammatory responses by these NPs led to inhibition of joint swelling in CIA mice also leading to minimal cartilage destruction and inflammatory cell infiltration in mice. Modified forms of CS such as thiolated glycol chitosan NPs have also been used for delivery of polymerized siRNA targeting TNF-α 84 for the treatment of RA. Other polymer-based self-assembling NPs such as cyclodextrin NPs for delivery of α-methylprednisolone 85 have also been used intravenously to treat mice with CIA.…”
mentioning
confidence: 99%